TINGKAT KERUSAKAN DAN STRATEGI PENGELOLAAN TAMAN HUTAN RAYA “PROF. IR. HERMAN JOHANNES” DI DESA KOTABES KECAMATAN AMARASI KABUPATEN KUPANG NTT - Nixon Rammang; M. S. Mahendra; Budiarsa Suyasa (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2014)
Prof. Ir. Herman Johannes Forest Park has suffered a serious damage from illegal logging and other destructives activities. This condition is worsened by lack of law enforcement and awareness on the importance of forest for the community. This study aims to determine level of damage from illegal logging, and formulate strategies to sustainably manageon the Prof. Ir. Herman Johannes Forest Park. Public perception was obtained by administering questionnaires and interviews through a purposive sampling method. The level of damage from illegal logging was assessed through identificationand measurement of damaged locations.SWOT analysis was used to formulate the management strategiesbased on identification of internal and external factors. Findings revealed that 5% of Prof. Ir. Herman Johannes Forest Park were damaged caused by illegal logging. The management of the Forest Park was challenged by illegal logging, forest encroachment, timber extraction for household use, slashing and burning practices, poor spatial planning, ineffective institutional arrangement, wildlife poaching, illegal grazing,and inadequate facilitates and staffs capability. In addition, there was lack of community involvement in the forest management. Aspects that appeared to require the most attention to improve the Forest Park includes consolidation of status and functions of the Forest Park, enhancement of surveillance and enforcement, improvement of the management effectiveness by establishing special division to manage the Forest Park, improvement of staffs capacity and infrastructures, rehabilitation of the damaged area, improvement of awareness to the impact of deforestation, and involvement ofindigenous and local communities on the Forest Park management (i.e. community-based forest monitoring, application of local wisdom in the forest management, community empowerment and economic development).